Altered Synaptic Transmission and Excitability of Cerebellar Nuclear Neurons in a Mouse Model of Duchenne Muscular Dystrophy - Kreko-Pierce, Tabita; Pugh, Jason R. (Frontiers in Cellular Neuroscience, 2022)
Duchenne muscular dystrophy (DMD) is generally regarded as a muscle wasting disease. However, human patients and animal models of DMD also frequently display non-progressive cognitive deficits and high comorbidity with neurodevelopmental disorders, suggesting impaired central processing. Previous work has identified the cerebellar circuit, and aberrant inhibitory transmission in Purkinje cells in particular, as a potential site of dysfunction in the central nervous system. In this work, we investigate potential dysfunction in the output of the cerebellum, downstream of Purkinje cell activity. We examined synaptic transmission and firing behavior of excitatory projections neurons of the cerebellar nuclei, the primary output of the cerebellar circuit, in juvenile wild-type and mdx mice, a common mouse model of DMD. Using immunolabeling and electrophysiology, we found a reduced number of Purkinje cell synaptic contacts, but no change in postsynaptic GABAA receptor expression or clustering in these cells. Furthermore, we found that the replenishment rate of synaptic vesicles in Purkinje terminals is reduced in mdx neurons, suggesting that dysfunction at these synapses may be primarily presynaptic. We also found changes in excitability of cerebellar nuclear neurons. Specifically, we found greater spontaneous firing, but reduced evoked firing from a hyperpolarized baseline in mdx neurons. Analysis of action potential waveforms revealed faster repolarization and greater after-hyperpolarization of evoked action potentials in mdx neurons, suggesting an increased voltage- or calcium- gated potassium current. We did not find evidence of dystrophin protein or mRNA expression in wild-type nuclear neurons, suggesting the changes observed in these cells are likely due to loss of dystrophin in presynaptic Purkinje cells. Together, these data suggest that loss of dystrophin reduces the dynamic range of synaptic transmission and firing in cerebellar nuclear neurons, potentially disrupting the output of the cerebellar circuit to other brain regions and contributing to cognitive and neurodevelopmental deficits associated with DMD.